Energy Expenditure and Intensity of Physical Activity in Soccer Referees During Match-Play - da Silva, Alberto Inácio (Asist Group, 2008)
The aim of this study was to determine the caloric expenditure and the intensity of physical activities performed by official soccer referees during a match expressed in Metabolic Equivalent (METs). The physical activity of referees accredited by CBF (Brazilian Confederation of Soccer) was video-recorded during twenty-nine official games of Paraná Championship (Brasil), Series A and B of the 2005/2006. Computerized video analysis was used to determine the time spent in 6 locomotor activities (standing still, walking, jogging, backwards running, running and sprint). The frequency and duration of each activity were recorded and these data were utilized to calculate the distance covered by the referee. Energy expenditure values were estimated, utilizing specific equations, from the time players spent in each motor activity. The referees observed in this study had a mean age of 38.9 ± 3.8 years, body mass of 86.1 ± 7.1 kg, stature of 1.80 ± 0.07 m and a body mass index of 26.5 ± 0.6 kg·m(-2). During match-play, referees covered an average distance of 9155.4 ± 70.3 meters (8411 - 9765), with a mean energy expenditure of 734.7 ± 65 kcal. This energy expenditure was significantly reduced in the second half: 359.9 ± 6.3 vs 374.7 ± 6.6 kcal (p = 0.006), and averaged to be moderate energy intensity (5 METs) with predominant utilization of the aerobic energy system. In total, during 67% of match-play the intensity was equal or lower than 3.8 METs and in 33% it was higher than 9.8 METs. The pattern of movement observed in the present study confirms that soccer refereeing may be considered as a highly intermittent exercise mode. The high to low-intensity activity ratio may be defined as 1:7.1. In conclusion, referees officiating in professional soccer matches in Brazil should perform a physical conditioning regime that provides the stamina required at this level and consume appropriate and adequate nutrition to meet the energetic demands for match-play.